1-(3,5-Dinitrobenzoyl)-3,3-dipropylthiourea - Sohail Saeed; Naghmana Rashid; Muhammad Sher; Seik Weng Ng; Edward R. T. Tiekink (Acta Crystallographica Section E, 2011)
The title thiourea derivative, C14H18N4O5S, features two substantial twists between its component fragments: the dihedral angle between the SN2C (thiourea) and ONC2 (amide) residues is 48.89 (7)° and that between the benzene ring and the amide residue is 30.27 (7)°. In the crystal, molecules are linked by bifurcated N—H...(O,S) hydrogen bonds, generating [001] supramolecular chains.